2002
DOI: 10.1017/s0952523802191097
|View full text |Cite
|
Sign up to set email alerts
|

Are primate lateral geniculate nucleus (LGN) cells really sensitive to orientation or direction?

Abstract: There is considerable controversy over the existence of orientation and direction sensitivity in lateral geniculate nucleus (LGN) neurons. Claims for the existence of these properties often were based upon data from cells tested well beyond their peak spatial frequencies. The goals of the present study were to examine the degree of orientation and direction sensitivity of LGN cells when tested at their peak spatial and temporal frequencies and to compare the tuning properties of these subcortical neurons with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 40 publications
10
76
1
Order By: Relevance
“…Orientation-selective dLGN cells have been reported in cats and primates, including macaques, owl monkeys, and marmosets (Smith et al, 1990;White et al, 1998;Xu et al, 2002), but the selectivity appeared less prominent in those species than what we reported here in mice. We converted the reported values in cats (Daniels et al, 1977;Vidyasagar and Urbas, 1982) to the same orientation selectivity index used here for comparisons.…”
Section: Orientation Selectivity In the Dlgncontrasting
confidence: 57%
“…Orientation-selective dLGN cells have been reported in cats and primates, including macaques, owl monkeys, and marmosets (Smith et al, 1990;White et al, 1998;Xu et al, 2002), but the selectivity appeared less prominent in those species than what we reported here in mice. We converted the reported values in cats (Daniels et al, 1977;Vidyasagar and Urbas, 1982) to the same orientation selectivity index used here for comparisons.…”
Section: Orientation Selectivity In the Dlgncontrasting
confidence: 57%
“…Consistently, a number of studies have reported direction-and orientation-selective responses in the dLGN of mice (Marshel et al, 2012;Piscopo et al, 2013;Scholl et al, 2013;, cats (Daniels et al, 1977;Vidyasagar and Urbas, 1982;Soodak et al, 1987), and monkeys (Smith et al, 1990;White et al, 1998;Xu et al, 2002;Cheong et al, 2013). In mice, DS cells appear to be more concentrated in the dorsal shell of the dLGN (Marshel et al, 2012;Piscopo et al, 2013), in which some of the DS RGCs terminate (Huberman et al, 2008(Huberman et al, , 2009.…”
Section: Dedicated Circuits For Direction Selectivity In the Visual Smentioning
confidence: 73%
“…It seems likely that direction biases for achromatic gratings arise from a slight spatial and temporal offset between sources of the S-cone signals and those of the L-and M-cone signals. We made no similar measurements on P-and M-cells, but previous work in other primates (White et al, 2001;Xu et al, 2002) suggests that their direction biases are much less prominent.…”
Section: Directional Selectivity From Receptive Field Asymmetriesmentioning
confidence: 86%